UPSTREAM HORIZONTAL MERGERS AND (THE ABSENCE OF) RETAIL PRICE EFFECTS - Ezrachi, A; Thanassoulis, J (2013)
The article explores the retail price effects of upstream and midstream horizontal mergers. It questions the prevailing assumption in merger review according to which such transactions will have similar effects on retail price as that of downstream horizontal mergers. The analysis illustrates how a sophisticated profit-maximizing merged entity may find it more profitable to enter into efficient contracts that seek to maximize the profit of the distribution channel, and so ensure that retail prices are not raised. The merged entity uses its market power and improved bargaining position to extract as much of that profit as possible from the retailer. We therefore argue that one cannot simply assume a direct link between the creation of market power upstream following a merger transaction, and the subsequent increase in retail prices. An analysis of the effects of upstream mergers on retail prices should call for a more nuanced appraisal that distinguishes the transfer of wealth within the operators in the distribution chain from the possible price impacts on final consumers. © The Author (2013). Published by Oxford University Press. All rights reserved.